El terror gótico latinoamericano de Mariana Enriquez como propuesta virtual en el museo Malba: una crítica social y de género - Silvia Beatriz Fernández (Les Cahiers ALHIM)
This article analyzes an interview conducted by Malena Rey with the Argentinian writer Mariana Enriquez at the Museo Malba in Buenos Aires, Argentina. There the interview addresses the condition of women in Latin America and the rest of the world. Firstly, an introspection is made from a gender philosophy point of view on the present day role women writers have and the place they have in the literary canon. Social critical perspective is developed as a result of the emerging crisis which covers the whole continent as of Covid-19 pandemic, which, in turn promoted an opening in the different way of understanding society and culture. Later, they address the social issue of inequity and violence from an analysis of the writers’ texts. This develops different issues in each one of the texts. Lastly, they bring up the importance of presenting these issues in the museum environment, the relevance of this topic and the urgent changes derived from these new types of writing.